COMPARATIVE STUDY OF CERVICAL RANGE OF MOTION, CERVICAL KINESTHESIA AND OCULAR MOBILITY IN SUBJECTS WITH CHRONIC NECK PAIN AND ASYMPTOMATIC SUBJECTS - Carrasco-Uribarren , A; Arroyo-Fraiz , B; Del-Villar-Arróniz , M; Ortúzar-Petreñas , M P; Ruiz de Escudero- Zapico , A; Cabanillas-Barea , S (Cuestiones de Fisioterapia, 2017)
Background: neck pain is a common symptom which affects 30-50 % of adults at least one day per year. Many of the patients with cervical pain have restriction on range of motion and sensorimotor dysfunction. The studies which compare aspects of cervical mobility, sensorimotor capacity and ocular mobility in asymptomatic subjects and cervical pain subjects are few. Objective: to compare different variables of function between asymptomatic sub-jects and subjects with chronic neck pain. Material and method: this is a transversal, observational and comparative study. Different variables were registered: pain intensity, neck disability index, cervical range of motion, upper cervical range of motion, cervical kinesthesia and ocular mobility. Results: 58 adults participated in the study (21 males (36,2 %) and 37 females, the average age was 41,98 ± 12,48), 29 subjects per group. The group with chronic neck pain showed restricted range of motion in extension, right and left rotation and right rotation in the flexion rotation test. In the slow eye movement, the chronic neck pain groups shows higher difficult than asymptomatic group (0,044). Conclusion: this study suggests that chronic cervical pain affects cervical spine mobility, cervical kinesthesia and ocular mobility when compared with asymptomatic subjects.